Challenges and Prospects of Village-Based Exotic Chicken Development Strategy in Amhara Regional State, Northwest Ethiopia (Global Journal of Science Frontier Research, 2012)
A study was performed from September 2009 to August 2011 to identify the major challenges and prospects of village-based exotic chicken production in Amahara Regional State. In this study ,village chickens were found raised mainly for income generation (76.0%) and home consumption (14.5%).The exotic chickens in this study were kept in scavenging type (61.5%) feeding with seasonal supplementation of grain .Among the maim problems related to poultry feed preparation are less availability of feed ingredients (48%) both in quality and quantity. It was found that individuals engaged in chicken rearing activities had higher preference for LOH (27%) than RIR (22.0%) breeds. But RIR breeds (52.5%) were more adapted the existing environmental conditions than LOH breeds. About 81.5% of respondents were found able to construct separate chicken houses and 94% of the respondents have incriminated disease as the most important constraint for chicken production.
Keywords: lohmann white/Rohde island red/exotic chicken breeds / mortality rates